Longer-run effects of antipoverty policies on disadvantaged neighborhoods - David Neumark; Brian J. Asquith; Brittany Bass (W.E. Upjohn Institute for Employment Research, 2019)
We estimate the longer-run effects of minimum wages, the Earned Income Tax Credit, and welfare on key economic indicators of economic self-sufficiency in disadvantaged neighborhoods. We find that the longer-run effects of the EITC are to increase employment and to reduce poverty and public assistance. We also find some evidence that higher welfare benefits had longer-run adverse effects, and quite robust evidence that tighter welfare time limits reduce poverty and public assistance in the longer run. The evidence on the long-run effects of the minimum wage on poverty and public assistance is not robust, with some evidence pointing to reductions and some to increases.
Keywords: I32; I38; J08; J21; J31; 330; Neighborhood poverty; minimum wages; EITC; welfare; employment